The different effects of molybdate on Hg(II) bio-methylation in aerobic and anaerobic bacteria - Wang, Lanjing; Liu, Hang; Wang, Feng; Wang, Yongmin; Xiang, Yuping; Chen, Yongyi; Wang, Jiwu; Wang, Dingyong; Shen, Hong (Frontiers in Microbiology, 2024)
In nature, methylmercury (MeHg) is primarily generated through the microbial metabolism, and the ability of bacteria to methylate Hg(II) depends on both bacterial properties and environmental factors. It is widely known that as a metabolic analogue, molybdate can inhibit the sulfate reduction process and affect the growth and methylation of sulfate-reducing bacteria (SRB). However, after its entry into the cell, molybdate can be involved in various intracellular metabolic pathways as a molybdenum cofactor; whether fluctuations in its concentration affect the growth and methylation of aerobic mercury methylating strains remains unknown. To address this gap, aerobic γ-Proteobacteria strains Raoultella terrigena TGRB3 (B3) and Pseudomonas putida TGRB4 (B4) as well as an obligate anaerobic δ-Proteobacteria strain of the sulfate-reducing bacteria Desulfomicrobium escambiense CGMCC 1.3481 (DE) were used as experimental strains. The growth and methylation ability of